Role of angiotensin receptors in the medial amygdaloid nucleus in autonomic, baroreflex and cardiovascular changes evoked by chronic stress in rats - Costa-Ferreira, Willian [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Crestani, Carlos C. [UNESP] (Wiley, 2021)
This study investigated the role of AT1, AT2 and Mas angiotensinergic receptors within the MeA in autonomic, cardiovascular and baroreflex changes evoked by a 10-day (1 hr daily) repeated restraint stress (RRS) protocol. Analysis of cardiovascular function after the end of the RRS protocol indicated increased values of arterial pressure, without heart rate changes. Arterial pressure increase was not affected by acute MeA treatment after the RRS with either the selective AT1 receptor antagonist losartan, the selective AT2 receptor antagonist PD123319 or the selective Mas receptor antagonist A-779. Analysis of heart rate variability indicated that RRS increased the sympathetic tone to the heart, which was inhibited by MeA treatment with either losartan, PD123319 or A-779. Baroreflex function assessed using the pharmacological approach via intravenous infusion of vasoactive agents revealed a facilitation of tachycardia evoked by blood pressure decrease in chronically stressed animals, which was inhibited by MeA treatment with losartan. Conversely, baroreflex responses during spontaneous fluctuations of blood pressure were impaired by RRS, and this effect was not affected by injection of the angiotensinergic receptor antagonists into the MeA. Altogether, the data reported in the present study suggest an involvement of both angiotensinergic receptors present in the MeA in autonomic imbalance evoked by RRS, as well as an involvement of MeA AT1 receptor in the enhanced baroreflex responses during full range of blood pressure changes. Results also indicate that RRS-evoked increase in arterial pressure and impairment of baroreflex responses during spontaneous variations of arterial pressure are independent of MeA angiotensinergic receptors.
Keywords: amygdala; angiotensin II; baroreflex; blood pressure; heart rate; Mas receptor